Peran Pendidikan Agama Islam Dalam Membangun Kesadaran Menjaga Kelestarian Lingkungan Di Green Islam Sekolah - Suriana Suriana (EL-EMIR Institute, 2026)
Current global environmental degradation demands solution-oriented approaches that engage the spiritual and moral consciousness of society. This study aims to analyze the role of Islamic Education (PAI) in fostering environmental awareness through the concept of Green Islam within the school environment. The research method employed is a qualitative approach, utilizing literature review and school-based case studies. The findings indicate that Islamic Education goes beyond teaching ritualistic aspects of religion; it integrates theological values such as the concept of humans as khalifah fi al-ardh (stewards on earth) who are responsible for environmental sustainability. The implementation of Green Islam in schools is carried out through the integration of an environment-based curriculum, the cultivation of eco-friendly behaviors (such as waste management and greening initiatives), and ecological dawah (proselytizing) in school religious activities. The main obstacles identified include the limitation of environment-focused religious textbooks and a lack of consistency in field implementation. In conclusion, Islamic Education plays a crucial role as a catalyst in shaping the character of an eco-literate younger generation through the internalization of green spiritual values.